2009
DOI: 10.1097/scs.0b013e3181a14d59
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Teres Major Muscle in Facial Paralysis Reanimation

Abstract: As a result of this preliminary study, we think that morphologic and neurovascular structures of this muscle is suitable for use in long-standing facial paralysis reanimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The teres major blood supply generally arises from a branch of the lateral circumflex scapular artery and is drained by 2 venae comitantes that run parallel to the artery. 3 In a few cases, the teres major blood supply arises from the thoracodorsal artery; therefore, in most people, if the flap can be pedicled on the circumflex scapular vessels without harvesting the subscapular vessels, the thoracodorsal artery can be preserved during teres major harvesting, thereby sparing the primary blood supply to the latissimus dorsi muscle. 1,3,4 Our series includes a case (patient 8) in which the thoracodorsal and circumflex scapular arteries arose distinctly from the axillary artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The teres major blood supply generally arises from a branch of the lateral circumflex scapular artery and is drained by 2 venae comitantes that run parallel to the artery. 3 In a few cases, the teres major blood supply arises from the thoracodorsal artery; therefore, in most people, if the flap can be pedicled on the circumflex scapular vessels without harvesting the subscapular vessels, the thoracodorsal artery can be preserved during teres major harvesting, thereby sparing the primary blood supply to the latissimus dorsi muscle. 1,3,4 Our series includes a case (patient 8) in which the thoracodorsal and circumflex scapular arteries arose distinctly from the axillary artery.…”
Section: Discussionmentioning
confidence: 99%
“…3 In a few cases, the teres major blood supply arises from the thoracodorsal artery; therefore, in most people, if the flap can be pedicled on the circumflex scapular vessels without harvesting the subscapular vessels, the thoracodorsal artery can be preserved during teres major harvesting, thereby sparing the primary blood supply to the latissimus dorsi muscle. 1,3,4 Our series includes a case (patient 8) in which the thoracodorsal and circumflex scapular arteries arose distinctly from the axillary artery. In this situation, using the latissimus dorsi as originally planned would have required an additional arterial anastomosis, but a chimeric flap was formed instead using the teres major muscle on a single arterial supply (circumflex scapular artery), simplifying the reconstructive process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no previous information about the area of the TM attachment footprint in literature. Earlier studies (Cleeman et al 2003;Pearle et al 2006;Buijze et al 2007;Giessler et al 2007;Morelli et al 2008;Alag€ oz et al 2009) investigated the tendon dimension immediately proximal to the attachment footprint without evaluation of the footprint itself. The present study has shown that the ratio between the area of the TM attachment and the LD attachment is approximately 2:1 (Table 1).…”
Section: Gageymentioning
confidence: 99%
“…Earlier investigations on the TM and LD anatomy have focused on the dimensions of the tendons close to the insertion (Cleeman et al 2003;Pearle et al 2006;Buijze et al 2007;Giessler et al 2007;Morelli et al 2008;Alag€ oz et al 2009). This information meets current needs only partially.…”
Section: Introductionmentioning
confidence: 99%